Modeling of Sonotrode System of Ultrasonic Consolidation With Transfer Matrix Method - Wang, Yin; Chen, Ziyan; Yu, Qing; Cheng, Fang (Frontiers in Materials, 2021)
To establish an efficient model for sonotrode system, a key part that continuously applies ultrasonic oscillation on metal foils to form solid state bond in ultrasonic consolidation equipment, this research presents modeling methods for sonotrode system. After an introduction to the construction of sonotrode system along with its operating principle, the transfer matrix method was adopted to build the model for the system consisting two ultrasonic transducers and one sonotrode. Simulation results of transfer matrix model were compared to that of finite element method. A prototype was fabricated and tested. A comparison of the resonance frequencies calculated by two modeling methods to the experimental result showed that the difference between transfer matrix model and prototype is 6.96% while the difference between finite element model and prototype is 9.26%. The proposed transfer matrix method is an efficient way to simulate dynamic performances for sonotrode system, which provide a better foundation for further optimization.